Analysis of the Use of Indonesian and Acehnese in the Learning Process at PAUD Farisa, Aceh Besar - Zari, Aufa Rafika Zari; Bahrun, Bahrun; Rizka, Sitti Muliya (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research aimed to describe the use of Indonesian and Acehnese languages in the learning process at PAUD Farisa, Aceh Besar District. This study used a qualitative approach with acase study method. The subjects of the study were three teachers, and data were collected through observation, interviews, and documentation. The findings show that Indonesian is predominantly used by teachers in all stages of the learning process. In the opening stage, Indonesian is used to greet students and convey the learning objectives. During the main activities, Indonesian is utilized to explain materials and provide instructions, while Acehnese is selectively used for storytelling, singing traditional songs, and strengthening social bonds. In the closing stage, Indonesian is again used to summarize lessons and deliver messages to children. Barriers to using Acehnese include limited culturally-based learning resources and teachers' lack of proficiency in effectively using the language. Teachers address these challenges by creating simple media, such as illustrated folk tales, and involving children in interactive discussions. These findings support Vygotsky's theory on the role of social interaction in children's language development and Chomsky's theory emphasizing the innate ability of children to acquire language. This study recommends that teachers balance the use of both languages, provide culturally-based learning materials, and involve parents in supporting the preservation of the Acehnese language at home and school.Kata Kunci: Acehnese Language; Early Childhood Education Learning Process; Indonesian Language; Language Use